Symmetry is its own reward: on the character and significance of Acheulean handaxe symmetry in the Middle Pleistocene. (24th April 2018) - White, Mark; Foulds, Frederick
Abstract: Abstract : Bilateral symmetry in handaxes has significant implications for hominin cognitive and socio-behavioural evolution. Here the authors show that high levels of symmetry occur in the British Late Middle Pleistocene Acheulean, which they consider to be a deliberate, socially mediated act. Furthermore, they argue that lithic technology in general, and handaxes in particular, were part of a pleasure-reward system linked to dopamine-releasing neurons in the brain. Making handaxes made Acheulean hominins happy, and one particularly pleasing property was symmetry.